Effect of organic matter Mucuna bracteata and antagonist microbes (Trichoderma viride and Trichoderma harzianum) on the domination of Root Gall Nematode Meloidogyne spp. in potato in the field - Raja Indra Rizki; Syahrial Oemry; Lisna Wita (Jurnal Agroekoteknologi, 2019)
ABSTRACT Root gall caused by Meloidogyne is one of threat for the production of potato plantation in Indonesia. Currently, biological controlling by using antagonist microbes and adding organic matters are more concerned to minimize the negative impacts for environment and human. Therefore, the objectiv of this research were to study the effect of organic matter Mucuna bracteata and antagonist microbes (Trichoderma viride and T. harzianum) on the domination of root gall nematode Meloidogyne spp. in potato in the field. This research was conducted in Plant Disease Laboratory, Agricultural Faculty of University Sumatera Utara, Medan and it was continued in the agriculture field in Karo Regency. The method used randomized complete block design non factorial with eight treatments (control, nematiside with active ingredient Karbofuran 3%,              M. bracteata, T. viride, T. harzianum, M. bracteata + T.viride, M. bracteata + T. harzianum and T. viride + T. harzianum) and five replications. The results showed that treatment Mucuna bracteata + T. viride was the best treatment to suppress the nematode’s population with 34.40 galls and final population was about 53.03.   Key words : Potato, Meloidogyne, Mucuna bracteata, Trichoderma viride,                                Trichoderma harzianum, Karbofuran 3%